Waste heat recovery of germanium doped magnesium stannide Mg2Sn0.75Ge0.25 - Ng, Guan Yi (2016)
For the past decades, renewable energy sources have piqued huge attention from all around the world. One of the alternatives to renewable energy which has shown great potential in its application is thermoelectric energy conversion, in which residual heat is converted into electricity through thermoelectric materials. This project is focused on bringing in n-type Germanium doped Magnesium Stannide as an environmental friendly and cost effective alternative to the state-of-the-art Lead (Pb) and Tellurium (Te) based thermoelectric materials for marine engine application. In this study, different composite ratios of Mg2(1+x)Sn0.75Ge0.25 were fabricated and analysed to achieve the best thermoelectric performance sample. 99+%purity Magnesium (Mg), Germanium (Ge) and Tin (Sn) powder were first ball milled and the resulting powders were then spark plasma sintering into pellet for characterizations with the ZEM instrument. This research has laid a foundation for further optimization of ball milling parameters and also the optimization of the Mg content used for ball milling to obtain a pure Mg2Sn0.75Ge0.25 phase. In addition, this report also has shown that the doping of Silver (Ag) has great potential in further improving the thermoelectric properties of Mg2Sn0.75Ge0.25